Peningkatan Pemahaman Membaca Berhitung Melalui Literasi Dan Numerasi Pada Siswa - Adinda Trias Ayu Syafira; Suaibatul Aslamiyah (Kreativasi : Journal of Community Empowerment, 2022)
The Covid-19 pandemic has had many impacts on the world of education, especially in the pre-school period for students. Many obstacles occur in the learning process at one of the MI schools in Gresik. The occurrence of learning barriers in grade 1 and 2 students is due to several factors that cause it, such as the lack of parental attention to children when at home, causing problems in the form of learning barriers for students. Thus causing a lack of motivation to learn in children. One of the efforts that can be done in this problem is to provide learning assistance to students who have learning disabilities. This mentoring process is carried out with the direction of the teacher and homeroom teacher of the student. The students we provide assistance with are recommendations from the homeroom teacher and approval from students' parents. Prior to the implementation of this mentoring process, students made direct observations in grades 1 and 2 in the learning process, the results of these observations were strengthened by interviews with the teachers and students. As a result of the tutoring assistance, students are better able to recognize the letters of the alphabet, fluently read and count in addition and subtraction categories.